The Relation of Upward Earnings Management Incentives and Corporate Governance Mechanism to Asymmetric Expense Behavior - hamideh esnaashari; shabnam javanmard (پژوهش‌های تجربی حسابداری, 2017)
This study is aimed to investigate the relation of upward earnings management incentives and corporate governance system to asymmetric expense behavior. This research uses the relation of logarithm of SG&A ratio and logarithm of operating revenue ratio to measure the asymmetric expense behavior. The corporate governance system is measured by 7 variables including board size, the percentage of nonexecutive directors ownership, the percentage of institutional shareholder ownership, ownership concentration, the percentage of major shareholders ownership, the percentage of management ownership, auditor type and a combined proxy. Return on assets (ROA) rate and changes of net income to total assets ratio are used to measure upward earnings management incentives. The sample consists of 98 firms listed in Tehran Stock Exchange (TSE) during the period from 2005 to 2014 considering certain criteria. GLS- pooled method is run to analyze data. The results reveal that expense behaves asymmetric on average. Additionally, expense behaves symmetric in firms with upward earnings management incentives with an annual Lag in comparison with others. Corporate governance system has no significant relation to expense behavior on average. This system does not increase asymmetric behavior of expense in firms with upward earnings management incentives.